Sentuhan Kasih Orang Tua Dalam Menumbuhkembangkan Karakter Remaja - Marisa Aulia Gea (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
This article discusses the role of loving touch from parents in developing adolescent character. In facing the often complex and dynamic realities of life, a person's character plays a crucial role in shaping an individual's personality. Adolescents, as a group that tends to oppose or oppose the values held by their parents, require special guidance and attention in character formation. Using descriptive qualitative methods and literature studies, this article explores an understanding of how a parent's loving touch can influence the formation of a teenager's character. The discussion covers important aspects such as forming healthy emotional relationships, developing positive values and attitudes, boosting self-confidence, and developing empathy and social skills. The results of the analysis show that consistent and positive loving touch creates a strong foundation for adolescents' emotional, social and moral development. Parental love creates an emotionally safe environment, allowing teens to feel loved, appreciated, and have a safe place to express themselves. Apart from that, the role of parents as good role models provides examples of positive behavior that can be internalized by teenagers. The aim of developing adolescent character includes preparing them to face future challenges, forming positive values, strong attitudes, and correct orientation towards life goals. Thus, this article provides an in-depth understanding of how a parent's loving touch contributes to shaping the character of teenagers, so that it can help form a generation that has positive character, empathy and strong social skills to face the various complexities of life in the future.